Age-Related Changes in Human Peripheral Blood IGH Repertoire Following Vaccination - Wu, Yu-Chang B.; Kipling, David; Dunn-Walters, Deborah K. (Frontiers in Immunology, 2012)
Immune protection against pulmonary infections, such as seasonal flu and invasive pneumonia, is severely attenuated with age, and vaccination regimes for the elderly people often fail to elicit effective immune responses. We have previously shown that influenza and pneumococcal vaccine responses in the older population are significantly impaired in terms of serum antibody production, and have shown repertoire differences by CDR-H3 spectratype analysis. Here we report a detailed analysis of the B cell repertoire in response to vaccine, including a breakdown of sequences by class and subclass. Clustering analysis of high throughput sequencing data enables us to visualise the response in terms of expansions of clonotypes, changes in CDR-H3 characteristics, and somatic hypermutation as well as identifying the commonly used IGH genes. We have highlighted a number of significant age-related changes in the B cell repertoire. Interestingly, in light of the fact that IgG is the most prevalent serum antibody and the most widely used as a correlate of protection, the most striking age-related differences are in the IgA response, with defects also seen in the IgM repertoire. In addition there is a skewing towards IgG2 in the IgG sequences of the older samples at all time points. This analysis illustrates the importance of antibody classes other than IgG and has highlighted a number of areas for future consideration in vaccine studies of the elderly.